Electromyographic and kinematic characteristics of baseball players with yips exhibiting different types of dystonic movements: A two-case report - Toshiyuki Aoyama; Kazumichi Ae; Takahiro Taguchi; Yuna Kawamori; Daisuke Sasaki; Takashi Kawamura; Yutaka Kohno (Heliyon)
The yips is a coordination impairment partly attributed to task-specific dystonia in athletes. While previous research focused on comparisons between control and yips groups, this study aimed to highlight interindividual differences in the yips symptoms of two baseball players with distinct dystonic movements through electromyographic and kinematic analysis. Twelve male college baseball players with two exhibiting throwing yips symptoms participated in this study. A three-dimensional motion capture system was used to analyze the kinematic features of throwing motion. Electromyographic data was recorded from the throwing upper limb. Case 1 showed markedly greater elbow flexion before ball release than the control baseball players, likely due to excessive and delayed muscle contraction of the biceps brachii. Case 2 showed intermittent activity of the middle deltoid muscle impacting shoulder abduction movement, resulting in action tremor of the upper limb. This study revealed two distinct types of dystonic movements in baseball players with throwing yips: excessive joint motion, which may be caused by impaired timing and amount of muscle activity, and action tremor, associated with intermittent muscle activity. These findings underscore the importance of individualized kinematic and electromyographic analysis to understand and treat yips symptoms.